As relações entre o aluno e o conhecimento escolar: o que pensam os alunos do sexto ano de uma escola pública e particular - Watanabe, Cláudia Akiko Arakawa (2012)
The present study aimed to verify the placement of students in the sixth grade in a public school and private school about the school knowledge. It is understood that the student s understanding of the sixth grade includes his/her way of thinking and acting, which is expressed in opinions about what happens inside and outside the school. So, by the relationship between the student and school knowledge, the research regarded the following specific objectives: verify the opinions of the students about the school discipline; to examine the assessment about the different teaching pedagogic methods considered as differentiated; analyze the role attributed to the historical school knowledge and finally, the contact that they maintain with the means of communication, the internet and television. Sixth eight students in the sixth grade were heard, aged between 10 and 11 years, with forty eight belonging in a public school and twenty students in a private school, both located in Santo André- SP. The methodological procedure for data collection consisted in the questionnaire application with 43 opened and closed questions. The results were interpreted in light of the Critical Theory of Society, with reference to the relationship between individual and society and using the concepts developed by the authors of the first generation of the Frankfurt School, as a reflection of the ideology of technology rationality in educational organization and student education, the cultural industry as an active in the formation of opinions issued by them and the alienation of individuals facing the objective conditions presented by the society. The main results showed the following similarities between students of two schools surveyed: recognition of the school as an educational institution having as purpose the conquest of material possessions, technology appreciation in the activities within and outside the school, the valorization of the more traditional pedagogic activities in the learning process, knowledge acquisition nonprofit immediate and future utilitarian with the indication of the historical wording, although considered theoretical, presented itself as one of the content more assimilated by them. As for the differences presented, it was observe that the private school students seem to rely more on school, considering it a means of upward social and economic, yielding to social and academic pressures, assuming their responsibilities in the name of efficiency, while the public school students appear to have greater uphold to technological rationality, believing more in the technique as a solution to their learning and looking for nice moments as a form of resistance in relation to the reality presented